Clinical and temporal patterns of severe pneumonia causing critical illness during Hajj - Mandourah Yasser; Al-Radi Assim; Ocheltree Ali; Ocheltree Sara; Fowler Robert A (BMC Infectious Diseases, 2012)
Abstract Background Pneumonia is a leading cause of hospitalization during Hajj and susceptibility and transmission may be exacerbated by extreme spatial and temporal crowding. We describe the number and temporal onset, co–morbidities, and outcomes of severe pneumonia causing critical illness among pilgrims. Method A cohort study of all critically ill Hajj patients, of over 40 nationalities, admitted to 15 hospitals in 2 cities in 2009 and 2010. Demographic, clinical, and laboratory data, and variables necessary for calculation of the Acute Physiology and Chronic Health Evaluation IV scores were collected. Results There were 452 patients (64.6% male) who developed critical illness. Pneumonia was the primary cause of critical illness in 123 (27.2%) of all intensive care unit (ICU) admissions during Hajj. Pneumonia was community (Hajj)–acquired in 66.7%, aspiration–related in 25.2%, nosocomial in 3.3%, and tuberculous in 4.9%. Pneumonia occurred most commonly in the second week of Hajj, 95 (77.2%) occurred between days 5–15 of Hajj, corresponding to the period of most extreme pilgrim density. Mechanical ventilation was performed in 69.1%. Median duration of ICU stay was 4 (interquartile range [IQR] 1–8) days and duration of ventilation 4 (IQR 3–6) days. Commonest preexisting co–morbidities included smoking (22.8%), diabetes (32.5%), and COPD (17.1%). Short–term mortality (during the 3–week period of Hajj) was 19.5%. Conclusion Pneumonia is a major cause of critical illness during Hajj and occurs amidst substantial crowding and pilgrim density. Increased efforts at prevention for at risk pilgrim prior to Hajj and further attention to spatial and physical crowding during Hajj may attenuate this risk.